Helmintofauna de anuros em campo nativo e área de cultivo no sul do Brasil - Portela, Aline Aparecida Bastos (2017)
The Campos Sulinos are grassy formations where there is high biodiversity, but the conservation of these grasslands has been neglected, while the degradation and the habitat advance at alarming rates. The impacts of habitat loss negatively affect the biodiversity, including the dynamics and composition of host and parasite communities. Despite the importance, the parasitic fauna of wild animals has been little studied, which motivated the development of the present study, aiming to contribute to the knowledge of the helmintofauna of anurans in the Campos Sulinos. Thus, we: (1) described the composition of the helminth community in seven anuran species in the Campos Sulinos region; (2) we compared native grasslands and agricultural area for parasite infection parameters using four species of host anurans, and (3) we tested whether environmental descriptors measured on multiple scales (local, spatial and landscape) influence the parasite infection metrics of the anurans in the Campos Sulinos region. Host anurans were sampled between January and February 2016, using the 'survey at breeding sites' method in 34 ponds (15 in agricultural and 19 in native grasslands) distributed in the Brazilian states of Santa Catarina and Paraná. We recorded 25 taxa of helminths belonging to the class Monogenea, Trematoda (Digenea), Cestoda and Nematoda, distributed in seven species of host anurans. Among these, we recorded by first time the genus Hedruris in Brazil, as well as presented the first informations on parasitic helminths for five of the seven species of host anurans. There was a significant difference between the native grasslands and the agricultural area regarding the structure of helminth communities in the hosts Aplastodiscus perviridis, Leptodactylus latrans, and Pseudis cardosoi. In addition, helminth indicators from natived and cultivated areas were found: the monogenetic Polystoma cuvieri (in Physalaemus cuvieri) and the cestode Ophiotaenia sp. (in Pseudis cardosoi) for the native grasslands, as well as the trematode Choledocystus elegans (in Leptodactylus latrans) and the plerocercoid larvae (Cestoda) (in Aplastodiscus perviridis) for agricultural cultivation. The prevalence of general parasitic infection was higher in the agricultural area (94%) than in the native grassland (84%). The infection parameters, by host species, usually showed a higher prevalence and intensity of infection in the agricultural area than in the native grasslands. However, we observed asymmetry in the parasite response, which seems to be related to host life history and parasite requirements, among other factors. The generalized regression models employed showed that the environmental descriptors explained the majority of parasite infection parameters in the studied anurans. The local descriptors (i.e. the ponds) were more important to explain the parasitism metrics, followed by the landscape descriptors. The descriptors related to the pond spatiality were not significant, suggesting that processes related to the parasite dispersion were of little importance in the studied region. Our work evidence that the agricultural cultivation negatively alters the metrics of anurans parasitism in the Campos Sulinos region.